Still an 'invisible crime'? Exploring developments in the awareness and control of human trafficking in Scotland. (September 2022) - Atkinson, Colin; Hamilton-Smith, Niall
In 2010 Korin Lebov published her article 'Human trafficking in Scotland', a state-of-the-field piece that reported on the nature and extent of human trafficking and the challenges in tackling this issue. Several important developments have occurred in the period since, including new enforcement measures, the first prosecutions and convictions for human trafficking in Scottish courts, the establishment of a dedicated policing unit within Scotland's new police service to tackle such crimes, the passage of specific human trafficking legislation through the Scottish Parliament, and, as a direct result of this legislation, the publication of a bespoke strategy by the Scottish Government to take action against human trafficking and support victims. This article draws upon the findings of a qualitative research study exploring the community impact of organized crime in Scotland and, in doing so, refracts advances in both public awareness of human trafficking and the policing response to this issue through the analytical prism of 'invisible crimes'. Ultimately, it traces the path of human trafficking from a peripheral and largely 'invisible' phenomenon to becoming a core issue of concern in Scotland's policing and community safety landscape.